The Utility of Beta 2 Microglobulin (B2M) as an Initial Diagnostic Tool for Oral Squamous Cell Carcinoma (OSCC): Evidence from a Malaysian Scenario - Narayanan, Maithrea Suresh; Kassim, Nur Karyatee; Liszen, Tang; Abdullah, Baharuddin; Omar, Julia; Mohd Hairon, Suhaily; Lazim, Norhafiza Mat (Bangladesh Journal of Medical Science, 2019)
Background: The delay in diagnosis of oral squamous cell carcinoma (OSCC) is a factor in rendering the poor prognosis, and recent research has explored the use of serum tumour markers such Beta 2 Microglobulin (B2M), to aid early diagnosis. However, despite a high incidence of OSCC in Southeast Asia, no studies on the clinical use of B2M in the region were found. Objectives: To determine if serum B2M level can serve as an initial diagnostic tool to indicate if a biopsy is warranted, and if so, to propose a local B2M serum reference value to identify OSSC patients. Methodology: Twenty-one patients were seen at Hospital Universiti Sains Malaysia (HUSM) for a one-year period, between June 2016 and June 2017, and equal number of healthy controls participated in the study. Apart from patient history, venous blood of approximately 5ml volume was collected from each subject at the pre-treatment stage and analysed by an Abbot ARCHITECT c8000 analyser using the immunoturbidimetry method. The results were analysed using ROC analysis and the Mann Whitney test. Results: Serum B2M levels showed a statistically significant increase (p<0.001) in patients compared to controls. The test was shown to have 90.5% sensitivity and 90.5% specificity. It was found to be a sensitive and specific serum tumour marker at a cut off value of 1.57mg/l to differentiate cases from controls. Conclusion: B2M is a sensitive and specific tumour marker to differentiate OSCC cases from controls. It is cost effective and minimally invasive, making it a potentially useful adjunct diagnostic tool in a high-risk patient pool. Bangladesh Journal of Medical Science Vol.18(4) 2019 p.729-735